Pengembangan E-Module Berbasis Inkuiri Terbimbing Pada Materi Sistem Reproduksi Manusia Terintegrasi Keislaman Kelas XI - Khasanah, Purnama Uswatun; Nirmalasari, Ridha; Lestariningsih, Nanik; Ayatusa'adah, Ayatusa'adah (BIOEDUSCIENCE, 2023)
Background: An educator must have expertise in developing teaching materials that can support and assist students in the learning process. One of the teaching materials that educators can develop is in the form of e-modules. This research aims to develop and create a teaching material product in the form of an e-module based on guided inquiry on the Islamic integrated human reproductive system material in class XI for Senior High School/MA. Method: The type of research used in this research is in the form of R&D (Research and Development), or what can be called research and development; the development model used is ADDIE. The ADDIE development model has several stages: Analysis, Design, Development, Implementation, and Evaluation. Research data was collected by validating e-module products, observing learning implementation, and using questionnaires from educators' and students' responses. The data from this analysis trial uses descriptive quantitative data. Product trials were conducted using small-scale tests in class XI MIPA 5 MAN Palangka Raya City. Results: E-modules developed to obtain material expert validation assessments have 91% results that fall into the "very feasible" criteria, media expert validation has 90.75% results that fall into the "very feasible" criteria, and interpretation expert validation has 78% results that fall into the "feasible criteria." At the same time, the results of the implementation observation were 82.62%, which is included in the "very good" criteria. The data from the educator response questionnaire have results as high as 75%, which falls into the "good" category, and the student response questionnaire has results of 82.16%, which is included in the "very good" category. Conclusion: From the data obtained, it can be determined that the guided inquiry-based e-module on the material of the integrated human reproductive system of class XI Islam is suitable for use in the learning process.